A framework proposal: analysing studies of circular economy with the institutional theory - Streit, Jorge Alfredo Cerqueira; Guarnieri, Patrícia; Ouro-Salim, Omar (Sustainability in Debate, 2023)
This study proposes a framework to facilitate the Circular Economy (CE) implementation cases analysis from the Institutional Theory (IT) perspective. The development of this theoretical framework was based on the levels of operationalisation of the Circular Economy and the types of isomorphic changes. To demonstrate the framework's applicability, we present a matrix classifying 59 case studies into nine quadrants (3 x 3). Subsequently, the papers' contents were discussed, revealing strategies and practices for institutional behavioural change that drive CE implementation at the micro, meso, and macro levels. Therefore, the results of this work contribute not only to academia by introducing a new way of analysing CE case studies but also to managers by discussing implemented or ongoing implementation cases.